2021
DOI: 10.1080/21655979.2021.1974650
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hsa_circ_0002024 as a prognostic competing endogenous RNA (ceRNA) through the hsa_miR_129-5p/Anti-Silencing Function 1B Histone Chaperone (ASF1B) axis in renal cell carcinoma

Abstract: We aimed to identify novel circular RNAs (circRNAs) as prognostic competing endogenous RNAs (ceRNAs) to serve as genetic biomarkers and therapeutic targets for renal cell carcinoma (RCC). High-throughput sequencing data of circRNAs from Gene Expression Omnibus (GEO) and of microRNAs (miRNAs) and messenger RNAs (mRNAs) from The Cancer Genome Atlas (TCGA) were retrieved to identify differentially expressed RNAs (DERNAs). DEmRNAs were subjected to weighted gene coexpression network analysis (WGCNA) to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Recent findings have greatly expanded our understanding of the role of ASF1B in the pathogenesis of various cancers, including prostate cancer, clear cell renal cell carcinoma, and cervical cancer [ 4 , 6 , 7 ]. Recent studies indicated that ASF1B was overexpressed in clear cell renal cell carcinoma, and its upregulation boosted cancer cell growth by activating the AKT pathway [ 4 , 28 ]. Han et al revealed that knockdown of ASF1B induced prostate cancer cell apoptosis by repressing the PI3K/Akt pathway [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have greatly expanded our understanding of the role of ASF1B in the pathogenesis of various cancers, including prostate cancer, clear cell renal cell carcinoma, and cervical cancer [ 4 , 6 , 7 ]. Recent studies indicated that ASF1B was overexpressed in clear cell renal cell carcinoma, and its upregulation boosted cancer cell growth by activating the AKT pathway [ 4 , 28 ]. Han et al revealed that knockdown of ASF1B induced prostate cancer cell apoptosis by repressing the PI3K/Akt pathway [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that up-regulation of ASF1B stimulated cancer cell proliferation, DNA replication and migration, accompanied by restrained cell cycle arrest and apoptosis ( Misiewicz-Krzeminska et al, 2013 ; Han et al, 2018 ; Zhou et al, 2019 ; Liu X. et al, 2020 ; Zhang et al, 2021 ), which was also consistent with our enrichment analysis of module genes ( Figure 2A ). In addition, several studies have underlined the important prognostic impact of ASF1B on a variety of cancers ( Corpet et al, 2011 ; Chen Z. et al, 2021 ; Feng et al, 2021 ). Another exciting finding was that ASF1B could regulate immune infiltration through affecting immune-related genes and pathways such as antigen processing and presentation and natural killer cell-mediated cytotoxicity ( Hu et al, 2021 ; Zhan et al, 2021 ), conferring its strong hints on potential immunotherapeutic target for several malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…Cenpf has a close relationship with MAPK (26, 27) and Wnt pathway (28). Antisilencing function 1b (Asf1b) had effects on cell proliferation, leading to abnormal nuclear structure and unique transcriptional features (29) and was often associated with various malignancies (30,31). According to the functional enrichment analysis, Asf1b was mainly enriched in the 'process utilizing autophagic mechanism' and 'biosynthesis of nucleotide sugars'.…”
Section: Discussionmentioning
confidence: 99%